From Fermentation to Preservation: The Making of Memory, Kimchi, and Belonging in Michelle Zauner’s Crying in H-Mart - Sanghamitra Dalal ([sic])
The article will read the biracial Korean American Michelle Zauner’s grief memoir, Crying in H-Mart (2021), which is suffused with raw articulations of agony and despair as it documents Zauner’s cancer-stricken mother’s last days. However, I will focus on how Zauner devotedly undertakes learning to cook and consume her mother’s dishes following her mother’s demise. As the gustatory sensation is induced in its entirety, she not only starts memorializing her mother but also starts learning how to embrace her biracial identity, which has often been a bone of contention between her and her mother. Therefore, evoking David Sutton’s concept of gustemology, which identifies food as a cultural site capable of reimagining the worlds displaced in space and time, I will examine how synesthesia, radiating through the process of creation and recreation of food and memory, could suggestively resuscitate the irrevocable loss, often suffered by migration and displacement, death, and bereavement.